2022
DOI: 10.1017/s0025315422000388
|View full text |Cite
|
Sign up to set email alerts
|

Site fidelity, population identity and demographic characteristics of humpback whales in the New York Bight apex

Abstract: Humpback whales (Megaptera novaeangliae) exhibit maternally driven fidelity to feeding grounds, and yet occasionally occupy new areas. Humpback whale sightings and mortalities in the New York Bight apex (NYBA) have been increasing over the last decade, providing an opportunity to study this phenomenon in an urban habitat. Whales in this area overlap with human activities, including busy shipping traffic leading into the Port of New York and New Jersey. The site fidelity, population composition and demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…2018; Zoidis et al 2021), including off the New York Bight apex (Brown et al 2022). The vast majority of those individuals have subsequently returned at least once to the GoM (Center for Coastal Studies, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2018; Zoidis et al 2021), including off the New York Bight apex (Brown et al 2022). The vast majority of those individuals have subsequently returned at least once to the GoM (Center for Coastal Studies, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously, humpback whale sightings have increased immediately south of the GoM (Brown et al 2018; Zoidis et al 2021) where they were historically uncommon (CETAP 1982). Photo-identification studies have shown that individuals in this newly populated area are primarily juvenile whales, but not exclusively (Brown et al 2018; Zoidis et al 2021), including off the New York Bight apex (Brown et al 2022). The vast majority of those individuals have subsequently returned at least once to the GoM (Center for Coastal Studies, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings illustrate that highly mobile sharks likely occupy an advanced trophic position within a highly complex, seasonal food web. The high reliance of several species on B. tyrannus could imply wasp-waist food-web conditions during the productive summer months (Madigan et al, 2012), whereby high abundances of forage fishes sustain a diverse suite of predators, including sharks, whales, and dolphins, the latter of which are also known to frequent the MAB during this period (Alter et al, 2022;Brown et al, 2022;Zoidis et al, 2021). As the distribution of mobile predators is predicted to expand northward due to warming waters (Bastien et al, 2020;Hammerschlag et al, 2022) and alterations to the distribution and movements of key prey groups (Friedland et al, 2019), understanding trophic ecology and resource use is critical to ensure the effective management of highly mobile species and their associated functional roles.…”
Section: Ordermentioning
confidence: 99%
“…The West Indies DPS is comprised of humpback whales that migrate from the breeding grounds near the West Indies to foraging grounds across the North Atlantic. Currently, humpback whales in the West Indies DPS use feeding grounds in the New York Bight, the Gulf of Maine, the Eastern Canadian Shelf, western Greenland, eastern Greenland, Iceland, and Norway (Katona and Whitehead, 1981;Baker et al, 1990;Hansen et al, 2019;National Oceanic and Atmospheric Administration, 2020;Brown et al, 2022;Kettemer et al, 2022;Heide-Jørgensen et al, 2023). The West Indies DPS exhibits strong site fidelity to specific foraging grounds, meaning that a whale seen in the Gulf of Maine will likely return to the Gulf of Maine, as documented in photoidentification and genetic studies (Palsbøll et al, 1995;Stevick et al, 2006).…”
Section: Introductionmentioning
confidence: 99%